1972
DOI: 10.1159/000208469
|View full text |Cite
|
Sign up to set email alerts
|

Pentose Phosphate Pathway of Erythrocytes in Uremia

Abstract: The transketolase activity (TKA) of red cells was determined in 286 controls and 50 patients with uremia. The TKA of the latter tended to exceed that of the controls, but statistically was not significant. In the uremic patients, the showed a positive correlation with serum creatinine, urea and potassium levels, and a negative correlation with the patients’ hemoglobin and TKA hematocrit. A 10-hour dialysis did not affect the TKA of the red cells in uremic patients, nor did uremic plasma inhibit or activate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We found that miR-146a-5p stimulated the expression of G6PD and TKT, the genes encoding two key enzymes of the oxidative and non-oxidative PPP branches, respectively. Interestingly, it was shown that transketolase (TKT) activity correlates with creatinine levels in uremic patients [18], which may possibly partially explain the observation that creatinine levels increased following miR-146a-5p transfection. Remarkably, other reports also demonstrated that creatinine concentrations can be affected by miRNAs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…We found that miR-146a-5p stimulated the expression of G6PD and TKT, the genes encoding two key enzymes of the oxidative and non-oxidative PPP branches, respectively. Interestingly, it was shown that transketolase (TKT) activity correlates with creatinine levels in uremic patients [18], which may possibly partially explain the observation that creatinine levels increased following miR-146a-5p transfection. Remarkably, other reports also demonstrated that creatinine concentrations can be affected by miRNAs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The red cell TKA increases in pernicious anaemia (4), and sometimes in uraemia (12), whereas it decreases in thiamine deficiency states (3), in post gastrectomy states (6), chronic alcoholism (8), dementia senilis (8) and hepatic porphyrias (11).…”
mentioning
confidence: 99%